Interactive Collaborative Robotics : Second International Conference, ICR 2017, Hatfield, UK, September 12-16, 2017, Proceedings /: Second International Conference, ICR 2017, Hatfield, UK, September 12-16, 2017, Proceedings. (2017) - Unknown
No abstract available